Germination of Capsicum Annum L. sedds after accelerated ageing and storge - Judith, Juni. (Universiti Malaysia Sarawak (UNIMAS), 2003)
A study was conducted to evaluate the effects of short period of accelerated ageing and storage on the germination of Capsicum annum seeds. The seeds were placed in desiccators to age for 0, 24, 48, 72, 96 and 120 hr at 40-42 ° C and 100% relative humidity. After accelerated ageing treatment, seeds were put in air-tight bottles and stored in two different environments: refrigerator (3-5°C) and ambient room (28-30°C) for 0, 1, 2 and 3 weeks. Germination of aged seeds decreased gradually after 48 hr and continued to drop until 120 hr ofageing. However, the 24 hours of accelerated ageing had the effect of increased the germination percentage as compared to 0 hr of ageing. Different environments of varying temperatures of storing seeds gave different results in percentage of seed germination. Seeds stored in refrigerator performed better than seeds stored in ambient room. Germination percentage of aged seeds decreased with increase in the period of ageing and storage.